Profitability, Leverage, Firm Size and Enviromental Performance Moderated Company Profile in Company Csr Disclosure - Padlah Riyadi; Novita W Respati; Ayu Oktaviani (Cebong Journal, 2022)
This study aims to determine and analyze the effect of profitability, leverage, firm size and environmental performance moderated by company profile variable on the CSR disclosures of companies listed the IDX in 2014-2019. Based on purposive sampling, there were 12 companies according to the research criteria multiplied by the number of 6 years of observation, 72 data were processed and analyzed using multiple linear regression. The result of simultaneously, the variables of profitability, leverage, firm size, environmental performance and company profile have a significant influence on CSR Disclosure. Partial testing shows that only leverage has a significant effect on CSR disclosure, while profitability, firm size, environmental performance and company profile have no significant effect on CSR disclosure. From direct testing